(untitled) (El Hilo de la Fabula, 2020)
Although the relationship between cinema and literature has always been very close, the comparative study of both semiotic systems, which has proved most fruitful in the case of screen adaptations of novels or short stories, has scarcely approached the mark left by films on specific literary works. With that aim in mind, the purpose of this paper is to show the influence of cinematic discourse on the narratological categories of time, space and characters in a short story by Aldecoa.